Reduction of joint nociception induced by formalin in rats treated ith low level laser therapy 670 or 830 nm - Karvat, Jhenifer; Kakihata, Camila M. M.; Malanotte, Jéssica A.; Pelissar, Daniele; Escher, Assis R.; Bertolini, Gladson R. F. (Medicina (Ribeirao Preto), 2015)
Study design: experimental study of cross-cutting nature. Objective: To evaluate the low level laser therapy (LLLT) effects, with a wavelength of 670 and 820nm, in nociception of Wistar rats submitted to hypernociception in his right knee. Methods: 18 Wistar rats, separated into 3 groups: G1 – untreated; G2 – treated with LBP 670 nm; G3 – treated with LBP 830 nm. For the hypernociception induction was injected into the tibiofemoral articular space 100 µL of 5% formalin. To evaluate nociception was used digital von Frey filament, both with pressure on the knee, as in the plantar region. The evaluations occurred: pre-injury (EV1), 15 (EV2), 30 (EV3) and 60 (EV4) minutes after hypernociception induction. For the treatment with LBP was used to 8 J/cm2, after EV2. Results: the withdrawal threshold, when the pressure was held at the knee, showed that 670 nm produced threshold elevation in EV3 and EV4, returning to values similar to those of EV1. For the plantar region, only 830 nm showed restoration of values in EV4, and was higher in EV3 when comparing with G1. Conclusion: Both wavelengths produced raising the paw withdrawal threshold in rats with knee hypernociception